"I Say Red, You Say Green": Students' Perception of "Speak English with Zach" Video Podcast for Speaking Practice - Wulandari, Hesti Ulin; Suharyanto, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This research aims to identify how students’ perception of the "Speak English with Zach" Video podcast is essential for optimizing its use as an educational tool, especially for speaking practice. Methodology: In this study, rsearchers used mixed methods, descriptive quantitative and qualitative. Researcher used questionnaires and interviews as data collection methods. The participants in this questionnaire were 54 students and ten students from the Interpersonal Speaking class at Universitas Muhammadiyah Surakarta. The object of this research is some videos from the podcast "Speak English with Zach" used as assignments in Interpersonal Speaking classes. Results: The data gathered from questionnaires and interviews showed that students' perceptions of using video podcasts for English-speaking practice were positive. As a medium for improving English language skills, students feel that videos can improve speaking skills and pronunciation, increase vocabulary and fluency in English, improve intonation and grammar, and increase their confidence. It is also found out about the difficulties that students experienced, such as the duration and script of the video, which made students less free to express themselves. Applications/Originality/Value: The research findings can help educators, curriculum designers, and podcast creators modify and improve the content of educational vodcasts for better learning outcomes.